Evolutionary aspects of thymology in pediatric practice - Yu. I. Rovda; N. N. Minyailova; A. V. Vedernikova; A. V. Shabaldin; I. K. Khalivopulo; S. F. Zinchuk; O. V. Shmakova; A. A. Lobykina (Медицинская иммунология, 2023)
The thymus is now considered a derivative of the immune system being, to greater extent, its central organ. Immunodeficiency states and immune dysregulation also depend on the quality of the thymus, which may be determined both genetically and by fetopathic approach as well as due to the possibility and mode of its intravital injuries, age-related involution over different periods of life. Not accidentally, there are various morphometric bipolar states of the thymus gland in the pediatric population (3-7%), whereas its size may be sufficiently larger or smaller than the reference variable values. In certain cases, the phenomenon of thymomegaly (for example, in newborns) is considered a result of genetic errors (neuro-endocrine-immune syndrome with thymomegaly) induced by the mutated Hox genes. This syndrome may also be associated with congenital heart disorders. Moreover, the excessive morbidity in respiratory infections (commonly, viral by their etiology) among young children with bipolar thymus conditions remains the subject of sharp discussions. Some works assessing immune status in the children subjected to forced thymectomy, e.g., during heart surgery, yielded quite controversial results, even in cases of subtotal removal of thymus gland.Dialectically, the concepts of “morphology” and “organ function” could not be separated from one another. The morphometric transformations in organs (even transient ones) occuring within the range of > 95 and < 5 percentiles, should be almost always underlied by a certain pathomorphosis which require verification of their causes and origin. Even today, however, the assessment of thymus pathomorphology in the deceased children is not always critical, being often descriptive. This situation is, probably, associated with extreme complexity of thymic morphology assessment. The final point seems to be not set in the discussion about immunodeficiency states or immune dysregulation among children with bipolar thymus transformations. This is due to current absence of reliable immune-mediated biomarkers, the limited availability of genetic diagnostics in primary immunodeficiency conditions, and a decreased interest of clinical science in the issues of bipolar conditions of the thymus gland at the early age, in the absence of longitudinal observations in this category of patients, etc. In this article, the authors attempt to draw attention of researchers to this problem.